O pacto nacional pela idade certa e a expectativa de superação das dificuldades de leitura no 1º ciclo do ensino fundamental em uma escola do campo em Inhangapi (PA) - PAIVA, Luciana Rodrigues de (2019)
The present work is based on a restlessness of daily teaching experience with a need to better understand the socio-educational relationship established in the 1st cycle of the fundamental aim to improve and improve the pedagogical practice in the multi-series classes in the municipality of Inhangapi, northeast of Pará. : What are the strategies developed by the PNAIC to overcome the difficulties of reading the students of the 1st cycle of the multi-grade class in a rural school in the municipality of Inhangapi? The general objective is to discuss how the strategies developed by the PNAIC are contributing to overcome the difficulties of reading students from multiserials classes in rural schools in the municipality of Inhangapi. The specific objectives are: to characterize the educational context of the municipality of Inhangapi and its implications in schools of the multisseriat class field; to understand the strategies of the PNAIC to overcome the difficulties in the process of appropriation of reading in Inhangapi / PA multisite classes and to analyze the relationship between the PNAIC propositions and the difficulties pointed out by the teachers of multi-seriate classes in Inhangapi / PA. Methodological basis was sought in the qualitative research and the methodological instrument chosen for field work was the on-site observation through a proposed questionnaire, which was analyzed from the dialogue with some theorists such as: Brazil through the National Compact Literacy in the Right Age (2012a, 2012b, 2014); Hage (2010); Ibernón (2009); Freire (1987, 1996, 2018), Rosa (2008), among others. The subjects involved were three servers of the public network being two teachers of multi-class and one pedagogical coordinator. In view of the results obtained, it can be seen that the PNAIC is part of the daily education of schools with multi-serials classes. However, it is not practiced effectively due to different factors such as lack of teaching material, pedagogical follow-up, continuous training, among others.